No Negative Priming Effect in the Manual Stroop Task - Mills, Luke; Kinoshita, Sachiko; Norris, Dennis (Frontiers in Psychology, 2019)
The negative priming effect is an increase in interference when the response to the target on the current trial corresponds to the response to the distractor word on a preceding trial. Contrary to the commonly held belief that the negative priming effect is ubiquitous in the Stroop task, in the original study by Neill (1977), negative priming was found only in the oral, and not the manual Stroop task. The present paper makes three empirical observations. First, we replicate the discrepancy in the finding of the negative priming effect in the oral versus manual Stroop tasks tested under identical conditions, where response mode could be the only the causal factor. Second, we point out that previous manual Stroop experiments reporting the negative priming effect confounded the effect of response repetition. Third, we report the analysis of the negative priming effect at the level of whole RT distribution, which revealed that the effect was absent throughout the RT distribution in the manual task, and it was of constant size across the RT distribution in the oral task. Implications of the results for conflict control in the Stroop task is discussed.